Transitioning to Sustainable Agriculture Requires Growing and Sustaining an Ecologically Skilled Workforce - Carlisle, Liz; Montenegro de Wit, Maywa; DeLonge, Marcia S.; Iles, Alastair; Calo, Adam; Getz, Christy; Ory, Joanna; Munden-Dixon, Katherine; Galt, Ryan; Melone, Brett; Knox, Reggie; Press, Daniel (Frontiers in Sustainable Food Systems, 2019)
In the face of rapidly advancing climate change, biodiversity loss, and water scarcity, it is clear that global agriculture must swiftly and decisively shift toward sustainability. Fortunately, farmers and researchers have developed a thoroughly studied pathway to this transition: agroecological farming systems that mimic natural ecosystems, creating tightly coupled cycles of energy, water, and nutrients. A critical and underappreciated feature of agroecological systems is that they replace fossil fuel- and chemical-intensive management with knowledge-intensive management. Hence, the greatest sustainability challenge for agriculture may well be that of replacing non-renewable resources with ecologically-skilled people, and doing so in ways that create and support desirable rural livelihoods. Yet over the past century, US agriculture has been trending in the opposite direction, rapidly replacing knowledgeable people with non-renewable resources and eroding rural economies in the process. Below, we suggest how US policy could pivot to enable and support the ecologically skilled workforce needed to achieve food security in the face of climate change.